Inhibition of Nuclear Transport of NF-ĸB p65 by the Salmonella Type III Secretion System Effector SpvD. - Nathalie Rolhion; R Christopher D Furniss; Grzegorz Grabe; Aindrias Ryan; Mei Liu; Sophie A Matthews; David W Holden (PLoS Pathogens)
Salmonella enterica replicates in macrophages through the action of effector proteins translocated across the vacuolar membrane by a type III secretion system (T3SS). Here we show that the SPI-2 T3SS effector SpvD suppresses proinflammatory immune responses. SpvD prevented activation of an NF-ĸB-dependent promoter and caused nuclear accumulation of importin-α, which is required for nuclear import of p65. SpvD interacted specifically with the exportin Xpo2, which mediates nuclear-cytoplasmic recycling of importins. We propose that interaction between SpvD and Xpo2 disrupts the normal recycling of importin-α from the nucleus, leading to a defect in nuclear translocation of p65 and inhibition of activation of NF-ĸB regulated promoters. SpvD down-regulated pro-inflammatory responses and contributed to systemic growth of bacteria in mice. This work shows that a bacterial pathogen can manipulate host cell immune responses by interfering with the nuclear transport machinery.